Persepsi Pengusaha Industri Sanitair Terkait Tingkat Literasi Keuangan - Dewi Sofiana (Universitas Negeri Malang, 2016)
The purpose of this research was to find perception Sanitair industrial central’s businessman associated of financial literacy level, financial literacy pattern, and impact of financial literacy to the people in surrounding. This research is using qualitative and designed for qualitative case study. The research is conducted in sanitair businessman’s community. The researcher did a research before having problems by using interviews and observations. The analysis techniques used are data reducing, data display and conclusion.The conclusion of the research showed that there are 3 levels; well literate, sufficient literate, and less literate. All of them are making a positive pattern and medium level. Financial literacy is not giving impact to the people in surrounding but it is giving impact to the businessman and through the industry it will give an impact to the people in surrounding. Keywords: Financial Literacy Level, Financial Literacy Pattern, Sanitair Industrial Central’s